Detrital apatite Lu–Hf and U–Pb geochronology applied to the southwestern Siberian margin. (18th February 2022) - Glorie, Stijn; Gillespie, Jack; Simpson, Alexander; Gilbert, Sarah; Khudoley, Andrei; Priyatkina, Nadezhda; Hand, Martin; Kirkland, Christopher L.
Abstract: Apatite is increasingly used in sedimentary provenance studies. However, detrital apatite U–Pb geochronology can be challenging due to the presence of non‐radiogenic Pb, its intermediate closure temperature ( 350–550°C) and/or age‐resetting by metamorphic/metasomatic processes. The Lu–Hf system in apatite has a higher closure temperature ( 675–750°C) and is, therefore, more robust to thermal resetting. Here we present the first detrital apatite Lu–Hf age spectra. We have developed a laser‐ablation Lu–Hf dating technique, using reaction‐cell mass spectrometry, that allows rapid cost‐effective analysis, required for detrital apatite studies. The method is best suited to Precambrian detritus, permitting greater radiogenic Hf ingrowth. Using samples from Siberia, we demonstrate: (1) excellent correlations between U–Pb and Lu–Hf dates for apatites from igneous protoliths; and (2) that Lu–Hf dating can detect primary age information in metamorphic grains. Hence, when used in tandem with U–Pb zircon and apatite geochronology, Lu–Hf apatite dating provides a powerful new tool for provenance studies.